Odpowiedzi

2009-11-03T09:15:33+01:00
(165/10-124/9)•18/33+11/5•(8/33-3/33)+2/11
___________________________________________=
(27/4+11/2)•1/7-3/4

(33/2-124/9)•18/33+11/5•5/33+2/11
=__________________________________=
(27/4+22/4)•1/7-3/4

[(297-248)/18 •18/33-1/3+2/11]
=_______________________________=
49/4•1/7-3/4

49/33-11/33+6/33
=_____________________=
7/4-3/4

44/33 4/3
=____________= ____________= 4/3
4/4 1
2009-11-03T11:20:38+01:00
Obliczenie dodam w załączniku jako jpg. Bo się wszystko rozsypuje jak wklejam w okno tekstowe. Wynik to 2.